Covid-19, Structural Breaks, and Capital Market Integration: Indonesian Evidence - Suriawinata, Iman Sofian; Setianingrum, Pristina Hermastuti; Prastuti, Doddi; Rusli, Devvy; Pranitasari, Diah (Jurnal STEI Ekonomi, 2023)
The main purpose of this study is to investigate the cointegration between the Indonesian capital market and the selected four international capital markets – namely the Australian Stock Exchange, the New York Stock Exchange, the London Stock Exchange, and the Hong Kong Stock Exchange - with the presence of two structural breaks due to the COVID-19 pandemic. The non-standard Johansen’s, as well as the ARDL methods of cointegration analyses, are applied to five capital market indices - consisting of the Jakarta Stock Exchange Composite Index (JSCI), ASX200, Dow Jones Composite Average (DJC), FTSE 100, and Han Seng Index (HSI) - from January 2019 to December 2020. VEC and ARDL models are employed to investigate the impact of structural breaks on Indonesia’s capital market performance. The results show that there are cointegration and long-run causality relationships between the Indonesian capital market and the four international capital markets during the pandemic, and the structural breaks significantly affect market performance. The COVID-19 pandemic has had a devastating global impact on capital markets, but an effective policy response by the Indonesian government might contribute to the relatively rapid recovery of Indonesia’s capital market.. There are two important implications relating to the findings of this study. Firstly, as capital markets around the world become more integrated, the benefit of international portfolio diversification decreases. However, stock price efficiency among capital markets increases. Secondly, the results of the Granger causality test might be useful for capital market investors in predicting the impact of the performance of one capital market on the performance of other capital markets.